Modeling and analysing of NSM strengthened RC beams with FRP strips using ANSYS - مبارك ثراء; عصام ناصر; بسام حويجة (Latakia University Journal -Engineering Sciences Series, 2023)
The Near Surface Mounted (NSM) technique is a promising strengthening approach, though unpopular due to unreliable prediction behavior of these beams at failure, Therefore, model will be developed in this study, using the finite element method (FEM) to simulate the behavior of NSM strengthened RC beams by modeling the debonding mechanism and taking the combined effect of tangential stresses and normal stresses that are applied to the strips when debonding failure occurs.The accuracy of this model was experimentally validated, and the model showed high agreement with the experimental results in load capacity, effective strain of FRP strips, Additionally, and the shapes of curves (deflection-load). Where the convergence ratio reached values ​​more than 97% for the failure load, and ranged between (97.5%-100%) for the effective strain of FRP strips, and the similarity between the experimental cracks and the ANSYS cracks was acceptable in places of formation, propagation, direction and length.